The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1128/jvi.02077-13
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T Cell Help Is Limiting and Selective during the Primary B Cell Response to Influenza Virus Infection

Abstract: Influenza virus vaccination strategies are focused upon the elicitation of protective antibody responses through administration of viral protein through either inactivated virions or live attenuated virus. Often overlooked in this strategy is the CD4 T cell response: how it develops into memory, and how it may support future primary B cell responses to heterologous infection. Through the utilization of a peptide-priming regimen, this study describes a strategy for developing CD4 T cell memory with the capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 90 publications
(103 reference statements)
7
80
0
Order By: Relevance
“…The results have shown that populating a host with CD4 T cell memory cells enhances the germinal center (GC) and Ab responses to influenza virus infection, suggesting that CD4 T cell help is a limiting factor in the B cell response to infection. Analysis of serum Ab specific for HA and NP by ELISA showed that a match between CD4 T cell help and Ab specificity, as well as HA-specific CD4 T cell memory, are needed for accelerated Ab responses (35). These results suggested that efforts to promote CD4 T cell immunity specific for HA would likely enhance long-lived neutralizing Ab responses, as CD4 T cells help promote B cell affinity maturation to plasma cells and B cell memory cells.…”
Section: Influenza Vaccinesmentioning
confidence: 85%
“…The results have shown that populating a host with CD4 T cell memory cells enhances the germinal center (GC) and Ab responses to influenza virus infection, suggesting that CD4 T cell help is a limiting factor in the B cell response to infection. Analysis of serum Ab specific for HA and NP by ELISA showed that a match between CD4 T cell help and Ab specificity, as well as HA-specific CD4 T cell memory, are needed for accelerated Ab responses (35). These results suggested that efforts to promote CD4 T cell immunity specific for HA would likely enhance long-lived neutralizing Ab responses, as CD4 T cells help promote B cell affinity maturation to plasma cells and B cell memory cells.…”
Section: Influenza Vaccinesmentioning
confidence: 85%
“…Our laboratory (80) and others (81) have shown that there is a deterministic linkage in specificities for T and B lymphocytes in response to enveloped viruses. In a mouse model of influenza infection, we discovered that the magnitude and kinetics of the HA-specific B cell response were accelerated when the host was armed with memory HA-specific CD4 T cells but were not helped in the presence of NP-specific CD4 cells and vice versa (80). Also, in tracking expansion of human CD4 T cells after vaccination, we determined that the HA-specific response, rather than to those specific for M1 and NP, correlated best with the neutralizing antibody response (56).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that antigen specificity of CD4 + T cells responding to influenza vaccination is linked to neutralizing antibody responses. 34,46 Mice that develop CD4 + T cell memory to HA exhibit enhanced neutralizing antibody levels and lower lung viral titers in comparison with mice bearing nucleoprotein-specific CD4 + T cell memory. 47 Linked specificity is also observed in humans who receive inactivated virus vaccine, which contains internal proteins in addition to the critical antigen HA.…”
Section: Ha-specific Cd4+ T Cells Are Linked To Neutralizing Antibodymentioning
confidence: 99%
“…Monovalent pandemic H1N1 and H5N1 vaccination studies show that HI titers correlate with HA-specific CD4 + T cell expansion, but do not track with NP-specific CD4 + T cell levels. 34,46 Moreover, circulating Tfh in humans are predominantly HA-specific. 48 These studies suggest a vaccine strategy that boosts protective antibody responses via memory CD4 + T cell induction could rely on HA-derived epitopes, despite closer sequence identity between seasonal and avian influenza internal antigens.…”
Section: Ha-specific Cd4+ T Cells Are Linked To Neutralizing Antibodymentioning
confidence: 99%